Mouthwash use and oral cancer: a systematic review and meta-analysis - Araújo, Jennifer Sanzya Silva de; Magalhães, Elma Izze da Silva; Lima, Hassan Lavalier de Oliveira; Cruz, Maria Carmen Fontoura Nogueira da; Thomaz, Erika Barbara Abreu Fonseca (Revista de Saúde Pública, 2023)
OBJECTIVE: This study aimed to investigate the effect of mouthwash use on the development of oral cancer. METHODS: Observational studies with adult/older adult populations that have examined the association between mouthwash use and oral cancer were included. Electronic search was performed in July 2022, with no time or language restrictions. PubMed/Medline, Embase, and Web of Science databases were used, and the search was extended to theses and dissertations libraries, Google Scholar, reference lists, and other sources. Methodological quality was assessed using the Newcastle-Ottawa Scale and quantitative data synthesis was performed by random effects meta-analysis, with different subgroup analyses and meta-regression. This revision was registered in Prospero (CRD42020143307). RESULTS: Of the 4,094 studies identified in the search, 15 case-control studies were included in the review, totaling 6,515 cases and 17,037 controls. The meta-analysis included 17 measures of effect from 15 case-control studies. The pooled OR was 1.00 (95%CI: 0.79–1.26, n = 17 studies), but it was 2.58 (95%CI: 1.38–4.82, n = 2 studies) among those who had used mouthwashes three times or more times a day, and 1.30 (95%CI: 1.10–1.54, n = 4 studies) among those who had used mouthwashes for more than 40 years. CONCLUSIONS: We f ound e vidence t hat a h igh f requency o f m outhwash u se m ay b e associated with an increased risk of oral cancer. However, despite the biological plausibility for this association, we suggest caution upon interpretation of our findings due to the few number of studies that have investigated the mouthwash use frequency, which should be considered. Therefore, we recommend that future studies assess, in detail, the frequency, duration, and content of mouthwashes to increase the strength of evidence for a possible dose-response effect of mouthwashes on oral cancer risk.